2017
DOI: 10.1016/j.rser.2016.11.050
|View full text |Cite
|
Sign up to set email alerts
|

Aggregated applications and benefits of energy storage systems with application-specific control methods: A review

Abstract: Distributed energy storage systems (ESSs) are becoming essential components for the operation of the increasingly complex electricity grid, where dispersed generation is causing powerflows occurring both top-down and bottom-up. Specifically, the combination of ESSs coupled with application-specific control methods can achieve the interdependent objectives of system stakeholders such as the system operator, electrical utilities, retailers, equipment vendors, the government and the electricity customers. The nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 71 publications
0
28
0
Order By: Relevance
“…As mentioned in Section 5.2, market rules in Western Australia were written to only allow generators to provide system support services, thereby excluding the use of batteries and other non-synchronous technologies [101,102]. This is despite energy storage being considered one of the most important mechanisms by which excess rooftop-PV-generated energy can best be integrated into existing power systems [110][111][112], in a state which has some of the highest daytime solar radiance in the world.…”
Section: Regulatory and Institutional Aspectsmentioning
confidence: 99%
“…As mentioned in Section 5.2, market rules in Western Australia were written to only allow generators to provide system support services, thereby excluding the use of batteries and other non-synchronous technologies [101,102]. This is despite energy storage being considered one of the most important mechanisms by which excess rooftop-PV-generated energy can best be integrated into existing power systems [110][111][112], in a state which has some of the highest daytime solar radiance in the world.…”
Section: Regulatory and Institutional Aspectsmentioning
confidence: 99%
“…In general, BESS can improve the efficiency of the power system by providing additional flexibility to TSOs and Distribution System Operators (DSOs), such as the provision of ancillary services, peak shaving, congestion management, and reduction of reserve provision from conventional units [70,100]. Figure 7 provides a taxonomy of different services and applications of BESS throughout the power system.…”
Section: Distributed Energy Storage Systems For Buildings Applicationsmentioning
confidence: 99%
“…Replacing thermal generators by an ESS, to perform frequency regulation (i.e., primary reserve) and spinning reserve (i.e., secondary reserve), results in regulating the system frequency at the fastest possible speed and with the minimum amount of energy utilised for that purpose [27]. In the work presented in [28], it is demonstrated that because of the fast acting nature of a battery-based ESS (with absence of mechanical inertia), periods of frequency excursion are minimised with the ESS to absorb energy faster than the response to over-frequency that can be provided by thermal generators, that follow the automatic generation control (AGC) signal.…”
Section: Esss Regulate Frequency and Provide Spinning Reservementioning
confidence: 99%